Fall Risk Assessment of Rural Elderly Population in Korea - Dahye Park; Hongsik Jo; Chul Ho Yoon; Eun Shin Lee; Min-Kyun Oh; Chang Han Lee (Annals of Rehabilitation Medicine, 2019)
Objective To investigate the risk factors for fall in the elderly population residing in rural areas of Korea and provide useful data for their prevention. Methods As part of farmers’ health promotion project, a retrospective study was conducted with a total of 350 elderly people recruited from March 2016 to December 2016. These subjects were divided into two groups: 254 non-fallers and 96 fallers. A person who fell to the floor at least once in the past year was defined as a faller. Participants were asked to visit the hospital once. The demographic characteristics, social environment, and educational levels were surveyed using a questionnaire. Physical examination was performed in the following order: cognitive function, lower leg strength and torque, body composition, and knee image test. Results Statistically significant factors for falls in univariate analysis were female gender, age, living alone, educational level less than middle school, skeletal muscle mass, Mini-Mental State Exam, knee osteoarthritis, hip torque, hip power mean, knee torque, and knee power mean. Multivariate analysis was performed to identify variables most relevant to falls among statistically significant factors in univariate logistic analysis. It was confirmed that female gender and age of 70–79 years were statistically significant factors related to falls. Conclusion Female gender and elderly status (70–79 years) are important risk factors for falls in rural areas underscoring the need for special attention when considering risk factors for falls among the elderly living in rural areas.